Global, regional, and national trends in ischaemic stroke burden and risk factors among adults aged 20 + years (1990–2021): a systematic analysis of data from the Global Burden of Disease study 2021 with projections into 2050 - Sibo Liu; Yanzhao Li; Xiaoyan Lan; Long Wang; Hang Li; Dean Gu; Mengxing Wang; Jinjie Liu; Jinjie Liu (Frontiers in Public Health)
BackgroundThe objective was to provide standardized, comprehensive, and updated estimates of the global, regional, and national burdens of and risk factors for ischaemic stroke (IS) in adults aged 20 years and older.MethodsThis was a population-based study (Global Burden of Disease, Injuries and Risk Factors Study 2021). Adults aged 20 years and older from 204 countries and territories and 811 subnational locations from 1990 to 2021 were included. The primary outcomes were IS-related age-standardized prevalence, mortality, disability-adjusted life years (DALYs), average annual percentage change (AAPC), and risk factors associated with DALYs.ResultsFrom 1990 to 2021, the global age-standardized prevalence of IS decreased from 1,309 (95% UI 1,151 to 1,481) to 1,266 (95% UI 1,120 to 1,423) cases per 100,000 population, with an average annual decrease of −0.12%. However, the prevalence increased notably in the middle sociodemographic index (SDI) regions and East Asia but remained stable in Southeast Asia. The total number of IS cases still increased significantly from 33.2 million to 68.4 million. During the same period, the overall age-standardized mortality for IS decreased from 116 to 70 cases per 100,000 population, with an average annual change of −1.60%. Similarly, the overall age-standardized DALYs for IS decreased by 35%, with an average annual change of −1.36%. The decrease in both the age-standardized mortality and DALY rates was correlated with the SDI, with the most rapid decrease occurring in high-SDI regions. Conversely, in subregions of southern sub-Saharan Africa, an increase was observed. Males consistently faced a greater burden of IS across all subgroups. High systolic blood pressure and high low-density lipoprotein cholesterol (LDL-C) levels consistently represented the most significant risk factors contributing to DALYs from 1990 to 2021.ConclusionGlobally, the total IS caseload has increased. Targeted strategies, such as metabolic risk control in high-SDI regions, low-cost interventions in middle-/low-SDI regions, and improved neuroimaging infrastructure in sub-Saharan Africa, are needed. Future research should focus on subtype-specific burdens, the legacy effects of COVID-19, and intervention cost effectiveness to guide policymakers in developing efficient strategies to combat the global burden of ischaemic stroke.